Vegetation‐Promoted Soil Structure Inhibits Hydrologic Landslide Triggering and Alters Carbon Fluxes. Issue 18 (20th September 2022) - Fan, Linfeng; Lehmann, Peter; Zheng, Chunmiao; Or, Dani
Abstract: Vegetation modulates rainfall‐induced shallow landslides in mountainous regions primarily via root reinforcement, canopy interception, and evapotranspiration. An understudied consequence of vegetation activity is the promotion of soil structure development—an important soil trait often neglected in hydromechanical models. Here we propose a novel mechanism for how vegetation‐promoted soil structure inhibits landslides via enhanced hillslope infiltration capacity and drainage that delay the onset of landslide triggering. The hydrologic alterations due to developed soil structure also decrease sediment yields and associated particulate organic carbon (POC) transport to rivers while promoting export of dissolved organic carbon (DOC) via hydrologic leaching. We identified global "hotspots" for soil structure impacts that support the putative role of vegetation‐promoted soil structure in observed POC/DOC partitioning. The incorporation of soil structure in Earth system models is not only important for infiltration‐runoff quantification, but also for its potential role in controlling regional and global carbon fluxes to oceans. Plain Language Summary: The triggering of rainfall‐induced landslides in mountainous regions is strongly modulated by vegetation. Previous studies have focused on root reinforcement, canopy interception, and transpiration effects, here we quantify the putative role of soil structure (e.g., macropores, soil aggregation) on hillslope hydrology and landslides. Results indicate that soil structure inhibits landslide triggering and decreases particulate organic carbon (POC) transfer to rivers while enhancing leaching of dissolved organic carbon (DOC) from vegetated terrains. We delineate global hotspots for soil structure impacts on organic carbon fluxes where observations of POC/DOC partitioning in large rivers support the soil structure hypothesis. Results suggest that incorporating soil structure into Earth system models is important for representing hydrology, landslides, and carbon dynamics in mountainous regions. Key Points: Vegetation‐promoted soil structure alters hillslope hydromechanical processes beyond root reinforcement Soil structure increases infiltration capacity and drainage thus affecting landslide triggering particularly under long intense rainfalls Soil structure decreases particulate organic carbon export from soils to streams but increases dissolved organic carbon export